Fase Perkembangan Bunga dan Kandungan Gula Endogen pada Pembungaan Hoya diversifolia Blume. - Ardie, Sintho Wahyuning (Jurnal Agro Teknologi Tropika, 2014)
Hoya diversifolia Blume (Asclepiadaceae) is one of Indonesianâs native plants that has potential to be developedas ornamental plant. The short flowering period in one year, however, is a big problem in developing Hoya as anornamental plant. The objective of this research was to determine the flower developmental phases and to study thecorrelation of endogenous sugar content with floral induction of H. diversifolia Bl. Morphological and anatomicalobservations showed that floral development of H. diversifolia Bl. consisted of 6 phases i.e. induction, early initiation,late initiation, differentiation, flower maturity, and anthesis. Total sugars and sucrose content were not significantlydifferent between inductive and non-inductive buds, while the amount of reducing sugar were significantly higher in theinductive buds (7.40 mg g-1 fresh weight) compared to non-inductive buds (4.14 mg g-1 fresh weight).Key words: Asclepiadaceae, flowering plant, Indonesian native ornamental plant